ChemInform Abstract: trans‐Diborylation of Alkynes: pseudo‐Intramolecular Strategy Utilizing a Propargylic Alcohol Unit. Issue 4 (January 2015) - Nagashima, Yuki; Hirano, Keiichi; Takita, Ryo; Uchiyama, Masanobu
Abstract The first trans‐selective diboration of alkynes is achieved using a pseudo‐intramolecular reaction of diboron with propargyl alcohols.